1993
DOI: 10.1111/j.1476-5381.1993.tb12843.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory actions of an N‐terminal peptide from human lipocortin 1

Abstract: An acetylated polypeptide corresponding to residues 2-26 of human lipocortin 1 was synthesized and the anti-inflammatory activity assessed in three models of acute inflammation in rat and mouse. In the carrageenin rat paw oedema test, the peptide produced a maximal inhibition of approximately 41% at the 3 h time point with a 10 gig dose. When rat paw oedema was induced by the injection of venom phospholipase A2, the peptide produced a significant inhibition (31%) at the top dose of 20 gig per paw. In the mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 10 publications
(7 reference statements)
1
37
0
1
Order By: Relevance
“…Since the study was designed to observe phorbol myristate acetate-induced c-fos activation, it is likely that several factors other than cPLA 2 also participate in this process. The importance of the N-terminal region in mediation of the anti-inflammatory function of glucocorticoids and inflammatory signal transduction has been reported by Flower and co-workers (41)(42)(43). In the study of neutrophil migration, a mechanism has been proposed that the N-terminus of ANX-I binds to a receptor-like molecule on the surface of the neutrophils (44).…”
Section: Fig 2 Production Of Gst-anx-i and Its Deletion Mutants In Ementioning
confidence: 97%
“…Since the study was designed to observe phorbol myristate acetate-induced c-fos activation, it is likely that several factors other than cPLA 2 also participate in this process. The importance of the N-terminal region in mediation of the anti-inflammatory function of glucocorticoids and inflammatory signal transduction has been reported by Flower and co-workers (41)(42)(43). In the study of neutrophil migration, a mechanism has been proposed that the N-terminus of ANX-I binds to a receptor-like molecule on the surface of the neutrophils (44).…”
Section: Fig 2 Production Of Gst-anx-i and Its Deletion Mutants In Ementioning
confidence: 97%
“…12 This contrasts with the situation within the host defence system where annexin 1 shows the full efficacy of the parent protein. 22 The nature of the annexin 1 receptor is also obscure. It has recently been suggested that the formyl peptide receptor (FPR) maybe important in this regard.…”
Section: Mechanism Of Annexin 1 Actionmentioning
confidence: 99%
“…It is required for the inhibition of NF-B activity by anti-inflammatory drugs (13) and has recently been shown to be a potential biomarker of therapeutic efficacy for IBD (14). The N-terminal region of annexin A1 comprising residues 2-26 (Ac2-26) has been well studied (15,16) and appears to have the same biological effects as the full-length protein (17). Analysis of a series of peptides based on the N-terminal sequence of annexin A1 showed that MC-12 (Ac-Gln-Ala-Trp) was the most potent inhibitor of NF-B activity in SW480 cells (13).…”
mentioning
confidence: 99%